Analysis BI Rate and Return of Third Party Fund On Rate of Third PartyFund onIslamic Banking in Indonesia - Ari Kristin Prasetyoningrum (Conference In Business, Accounting, And Management (CBAM), 2015)
The  concept  of  Sharia  banks  is  different  with  interest-based  conventional  banks. Profit  sharing system in the Sharia  banks has unique characteristics because it must always be submissive and obedient to the rules and principles  of sharia.  This has implications  for the entire activities ofSharia  banks, Sharia  banks will thus experience the risks caused by its activities. Depositors  entrust their funds for Sharia banks to be managed by the bank so that it will generate  a return  for the depositor  and the bank. Therefore, Sharia  banks should be run in a professional  manner so as to maintain the loyalty of its customers and is able to provide a return that is generally competitive. The objective of this research  is to examine the influence Return of the Third Party Funds (Return of TPF) and the BI rate on the rate of Third Party Funds (Rate of TPF).  This research  is an explanatory  research using path analysis  model and census technique on Sharia Business Board (SBB) in Indonesia.  data used in this research  is a secondary  data derived from historical  data of Islamic banking from the data obtained through the official website of Bank Indonesia in the period of 2010 - 2012.  The results  of this research  indicate  that:  1) BI rate  significantly  influences Return of Third Party Funds resulting  in p-value <0,01  with the direction  of a negative relationship, 2) Return of Third Party  Funds significantly effects on the rate of Third Party  Funds with the direction  of positive relationships, and 3) BI rate significantly negative effect on the rate of Third Party Funds.  Keywords: Islamic Bank, BI Rate, Return, TPF (Third Party Funds)